Songsong Pemilihan Kepala Daerah (PILKADA) 2024: Upaya Penguatan Literasi Politik bagi Pemilih Pemula di Takengon, Aceh Tengah - Latif, Ikhwan Rahmatika; Afriandi, Fadli; Saputra, Ilham Mirza; Marefanda, Nodi; Marlizar, Desi; Sari, Nurhalista; Iqbal Aziz, Chairul; Fahlevi, Reza; Alqarni, Wais; Akbar, Arif (Pusat Penelitian dan Pengabdian Kepada Masyarakat STAIN Teungku Dirundeng Meulaboh, 2025)
Political literacy refers to the ability of individuals to understand political systems, processes, and information to actively participate in political decision-making. For first-time voters, political literacy is crucial as it forms the foundation for making rational choices, particularly in the 2024 regional elections (Pilkada). This community engagement initiative aims to enhance the level of political literacy among first-time voters through socialization, political literacy education, and comprehension tests covering four key indicators: understanding the political system, knowledge of the Pilkada process, critical evaluation of political information, and participation in Pilkada. The study employed a Google Form-based questionnaire distributed to 40 respondents from 11th and 12th-grade students in both science (IPA) and social sciences (IPS) streams. The analysis results revealed that the average comprehension level of respondents ranged between 70% and 85%, with minor variations across indicators and groups. Respondents demonstrated strong understanding in the